﻿Antiproliferative activity of a new derivative from the class of N-glycoside of indolo[2,3-a]pyrrolo[3,4-c]carbazoles - Marina P. Kiseleva; Larisa M. Borisova; Galina B. Smirnova; Yulia A. Borisova; Anna V. Lantsova; Ekaterina V. Sanarova; Lyudmila L. Nikolaeva; Lydia V. Ektova; Marina V. Komarova (Belgorod National Research University, 2022)
Introduction: The creation of highly effective original anticancer drugs remains an urgent direction of scientific research in tumor therapy. One of the promising groups in this regard is ﻿indolocarbazoles﻿ and their derivatives, which are capable of initiating various pathways of tumor cell death. The aim of the study was to evaluate an antiproliferative activity of a new, Russian derivative of N-glycoside substituted ﻿indolocarbazole﻿ 6-amino-12-(α-L-arabinopyranosyl)indolo[2,3-a]pyrrolo[3,4-c]carbazole-5,7-dione (LCS-1208) on models of transplantable tumors of mice and on human tumors in Balb/c nude mice. Materials and methods: ﻿Indolocarbazole﻿ sensitivity to LCS-1208 was assessed on transplantable tumors of mice - lymphatic leukemia L-1210, cervical carcinoma (CC-5), and colon adenocarcinoma (CAC) by five-fold intraperitoneal administration (ip) of the LCS-1208 substance in single doses of 50, 75, 100 mg/kg. Investigation into the effectiveness of the LCS-1208 lyo dosage form was performed on subcutaneous xenografts of human colon cancer SW620 by an intravenous administration (iv). The antitumor effect was evaluated by the tumor growth inhibition (TGI) and an increase in life span (ILS) of the treated animals as compared with the control ones. Evaluation of specific antitumor activity on xenografts was performed according to the tumor/control (T/C%) criterion (maximum criterion T/C≤42%). Results and discussion: According to the results of the study, the most sensitive to the action of the LCS-1208 substance in the case of an ip administration of a total dose of 375 mg/kg were CAC with TGI=97-62%, p≤0.001 up to 16 days after the treatment, and ILS=36% (criteria for TGI≥70% and ILS≥25%). On xenografts of a human colon cancer SW620, the effectiveness of the LCS-1208 lyo drug dosage form within the range of total doses from 50 to 150 mg/kg in case of iv to Balb/c nude mice was set at T/C = 35-2% (criterion T/C<42%). Conclusion: The presented results suggest possible effectiveness of LCS-1208 in treatment of colon malignant tumors of humans.